Crystal and molecular structure of bis(4-bromo-N-(diethylcarbamothioyl)benzamido)nickel(II) complex - Binzet, Gun; Flörke, Ulrich; Külcü, Nevzat; Arslan, Hakan (European Journal of Chemistry, 2012)
We report the synthesis of bis(4-bromo-N-(diethylcarbamothioyl)benzamido)nickel(II) complex of an benzoylthiourea derivative formulated as C24H28Br2NiN4O2S2. The structure of compound has been determined by single-crystal X-ray diffraction analysis. It crystallizes in the monoclinic space group, P21/c with unit cell dimensions of a = 12.9099(17) Å, b = 15.264(2) Å, c = 14.0287(19) Å, β = 92.140(4)o and V = 2762.5(6) Å3. In this compound, the nickel atom is coordinated by two sulphur and two oxygen atoms from two 4-bromo-N-(diethylcarbamothioyl)benzamide molecules forming an distorted square-planar geometry.